استخدام طريقة المناقشة في مجموعات صغيرة لترقية مهارة القراءةلدى طلاب الصف الثامن بمدرسة الأزهر المتوسطة الإسلامية 18 سلا تيجا - Al Amin, Muhammad Rifqi; Rusliyani, Dewi (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to investigate the use of the Small Group Discussion (SGD) method in improving the reading skills of eighth-grade students at SMP Islam Al-Azhar 18, Salatiga in the 2023/2024 academic year. The research is a classroom action research (CAR) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 25 students. The findings indicate a significant improvement in students’ reading skills after the implementation of the Small Group Discussion (SGD) method, as reflected in the increase in student learning outcomes. The pre-cycle results showed that 60% (15 students) had not yet met the Minimum Mastery Criteria (KKM), set at 80, while 40% (10 students) scored above the KKM. In the first cycle, 64% (16 students) met the KKM, while 36% (9 students) did not. This demonstrates an improvement from the pre-cycle to the first cycle. To achieve the expected completion indicators, further learning improvements were carried out in the second cycle. After the second cycle, the results were satisfactory, with 84% (21 students) meeting the KKM and 16% (4 students) still not achieving it. This shows that the learning improvements in the second cycle were successful, and the expected indicators were properly achieved.